Reservation System for Hotel Fox (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A hotel reservation system is a platform for users such as customers and admin where customer can book their desired room. The summary of the whole system is how it works in today’s world. In our study, the problems of our client are handling data accurately and data lost because they use a manual process. Our objective is to spend less time searching and retrieving files and increase the security between the management and staff. First, we interviewed our client to collect information. Then, we want to know their problems in their hotel reservation process. We decided to develop their reservation system as a computer-based system to allow the hotel to provide quick service for guests. The process of our hotel reservation system is as follows. The user must log in to the system access the dashboard. Then, the user will see buttons, such as registration form, reservation form, and list of customers and available rooms. Each button has its function. A hotel reservation system plays an important role in Hotel Fox because the hotel greatly benefited from our proposed system. They will not use a manual system to store customer’s status and room availability anymore. They will have a great advantage on their time-consuming task to find the information of a single customer.
Keywords: hotel, reservation, reservation system, client